Investigation of indolamine 2, 3 dioxygenase (IDO‐1) gene expression by real‐time PCR among patients with lung cancer. Issue 8 (22nd January 2019) - Haji Mazdarani, Mojtaba; Jafarikia, Milad; Nemati, Fahimeh
Abstract: Introduction: The aim of this study was to evaluate the expression of IDO‐1 gene and cancerous grades of non‐small cell lung cancer (NSCLC) and its subclasses among patients with lung cancer using real‐time polymerase chain reaction (PCR). Materials and Methods: A total of 35 clinical samples were collected from patients with NSCLC. To evaluate the IDO‐1 gene after the extraction of RNA and complementary DNA (cDNA) synthesis using real‐time PCR, the expression of the gene was investigated. The western blot analysis method was used for protein expression. Results: The highest grade, IIIa grade included six patients (17.1%). Approximately 74% of adenocarcinoma cases were in T‐categories of lung cancer and 25% of patients in IIIa grade. Patients in the IIA and IIB categories belong to the SCC subclass. Results showed that the expression of INDO 5.22 fold gene was more common in patients with lung cancer than NSCLC. Protein expression in western blot analysis in patients compared with normal 3.22 fold change increased. Conclusion: The evidence shows that IDO‐1 is a key parameter that inhibits antitumor immune responses in humans. This study has added interesting data to the IDO community for analyzing the expression of cancerous human cancer cells and cancer tissue in humans. The results showed that IDO‐1 not only participates in the process of escape from tumor immunity but can also contribute to the safety of the pretumor area. A wide variety of observed IDO‐1 expression values ​​among patients may present serious barriers to the clinical performance of anti‐ IDO strategies at present. Abstract : Linear and logarithmic diagrams of real‐time PCR amplification and temperature curve for the INDO gene.